2023
DOI: 10.1111/nph.19126
|View full text |Cite|
|
Sign up to set email alerts
|

Expression quantitative trait loci mapping identified PtrXB38 as a key hub gene in adventitious root development in Populus

Tao Yao,
Jin Zhang,
Timothy B. Yates
et al.

Abstract: Summary Plant establishment requires the formation and development of an extensive root system with architecture modulated by complex genetic networks. Here, we report the identification of the PtrXB38 gene as an expression quantitative trait loci (eQTL) hotspot, mapped using 390 leaf and 444 xylem Populus trichocarpa transcriptomes. Among predicted targets of this trans‐eQTL were genes involved in plant hormone responses and root development. Overexpression of PtrXB38 in Populus led to significant increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…To further amplify the potential benefits of SA catabolism, we repeated these experiments using a P. tremula x P. alba INRA 717-1B4 mutant that overexpresses the PtrXB38 gene [37]. This mutant has been shown to produce significantly higher concentrations of salicin in the roots (Figure S4).…”
Section: Effects Of Epistatic Interactions That Benefit Sa Catabolizersmentioning
confidence: 99%
See 1 more Smart Citation
“…To further amplify the potential benefits of SA catabolism, we repeated these experiments using a P. tremula x P. alba INRA 717-1B4 mutant that overexpresses the PtrXB38 gene [37]. This mutant has been shown to produce significantly higher concentrations of salicin in the roots (Figure S4).…”
Section: Effects Of Epistatic Interactions That Benefit Sa Catabolizersmentioning
confidence: 99%
“…Sorbitol (75 µL of 1mg/mL aqueous solution) was added to the first extract as an internal standard [37]. The two extracts were combined, and a 1 mL aliquot was dried under nitrogen for analysis.…”
Section: Metabolite Analysismentioning
confidence: 99%
“…Since its publication, the authors of Yao et al (2023) have identified an error in their article. An image for 'OE-72' was duplicated in Fig.…”
mentioning
confidence: 99%